ENGLISH TEACHING IMPLEMENTATION IN INDONESIAN PESANTRENS: TEACHERS’ DEMOTIVATION FACTORS - HABIBI, AKHMAD; SOFWAN, MUHAMMAD; MUKMININ, AMIRUL
This qualitative inquiry is aimed at analysing demotivation factors of teachers inIndonesian Pesantrens(Islamic Boarding School) in implementing EFL teaching.The research is appropriately undertaken as a qualitative research with a case studyapproach. The research sites for this study are two Pesantrens in Jambi, one ofIndonesian Provinces. Eight English teachers were involved as the participants toprovidebroader perspectives of the participants in relation to the EFL teaching. Theresearcher usedthree kinds of instruments in collecting the data; interview, focusgroup discussion, and document review. The researcher conducted the observation,interviewed the teachers, held focus group discussion, and collected relateddocuments to support the data.To assess the trustworthiness of the research, theresearcher did triangulation, member checking and reflexivity. The findings describeworking condition (financial matter and working overload); curriculum (rapidchanging of Indonesian curriculum and lack of teaching and supporting materials);facilities (classroom temperature and over-crowded classroom); students (lack ofbasic knowledge and lack of motivation).